Usefulness of Transurethral Incision as a Primary Treatment of Ureterocele in Children. Issue 4 (1996) - Takeuchi, Ichiro; Nonomura, Katsuya; Kanagawa, Koichi; Yamashita, Tetsufumi; Kakizaki, Hidehiro; Gotoh, Toshiaki; Koyanagi, Tomohiko
Abstract : Seventeen patients (11 girls and 6 boys, with bilateral cases in 4 for a total 21 units), in whom ureterocele was diagnosed at from 5 days to 11 years old, were treated with transurethral incision as a primary treatment. Urinary tract infection was the most common presenting sign in 8 patients. A voiding disturbance was observed in 10 patients. Seven units were diagnosed as intravesical ureteroceles of a single system and 14 units as ectopic ones (12 associated with the duplex system and 2 with a single system). De novo reflux occurred in 12 units, but in 5 units resolved spontaneously. All 5 refluxes in mate units improved, and 2 refluxes in the contralateral ureter also disappeared. The control of infection became easy in all patients except for one with a sphincteric ureterocele. Split renal function onT 99 m c -diethylenetriamine pentaacetic acid scintigraphy was prominently improved in 5 systems (35.7%) and normal kidney growth was obtained in 11 systems (78.6%). A total of 13 affected units (68.4%), including 7 units (6 intravesical and 1 ectopic) for which transurethral incision seemed to have been the sole necessary treatment, were saved. We believe that transurethral incision of ureteroceles is a very useful technique as a primary treatment for all types of ureteroceles in children of all ages.